2017
DOI: 10.15430/jcp.2017.22.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative Effects ofAndroctonus amoreuxiScorpion andCerastes cerastesSnake Venoms on Human Prostate Cancer Cells

Abstract: The present study evaluated the effects of Androctonus amoreuxi scorpion venom, Cerastes cerastes snake venom and their mixture on prostate cancer cells (PC3). An MTT assay was used to determine the anti-proliferative effect of the venoms, while quantitative real time PCR was used to evaluate the expression of apoptosis-related genes (Bax and Bcl-2). Furthermore, colorimetric assays were used to measure the levels of malondialdehyde (MDA) and antioxidant enzymes. Our results show that the venoms significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Al Asmari and Khan [15] studied the antitumor effect of the venom of Leiurus quinquestriatus on the chemical effect of skin cancer in mice and obtained positive results. Akef et al [16] found that Androctonus amoreuxi scorpion venom has cytotoxic and antiproliferative effects against prostate cancer. Besides the anticancer effect studies of scorpion venom, antimicrobial effect researches have been carried out successfully.…”
Section: Resultsmentioning
confidence: 99%
“…Al Asmari and Khan [15] studied the antitumor effect of the venom of Leiurus quinquestriatus on the chemical effect of skin cancer in mice and obtained positive results. Akef et al [16] found that Androctonus amoreuxi scorpion venom has cytotoxic and antiproliferative effects against prostate cancer. Besides the anticancer effect studies of scorpion venom, antimicrobial effect researches have been carried out successfully.…”
Section: Resultsmentioning
confidence: 99%
“…Such enhanced activity of drug-loaded phytosomes compared with the pure drug have previously been reported with QRT, and could be due to improved intracellular bioavailability [ 47 ]. In addition, the incorporation of SV into the novel formulation has also contributed to the improved cytotoxicity of QRT [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Asmari, Islam, and Al‐Zahrani (2016) demonstrated anticancer activity of Androctonus crassicauda against the HCT‐8 cell line (human colorectal adenocarcinoma), which showed 98% cell death after 24 h at a concentration of 100 μg/mL. Akef, Kotb, Abo‐Elmatty, and Salem (2017) reported anticancer characteristics of Androctonus amoreuxi against the PC‐3 cell line (human prostate adenocarcinoma), exhibiting 93% cancer cells death within 24 h at a concentration of 5.58 μg/mL. A. amoreuxi , at a concentration of 0.61 μg/mL showed anticancer activity against the MCF‐7 cell line (human breast adenocarcinoma) with 83.7% cancer cells death within 24 h (Salem, Shoukry, Teleb, Abdel‐Daim, & Abdel‐Rahman, 2016).…”
Section: Scorpion Venoms: Promising Anticancer Agentsmentioning
confidence: 99%